The effect of smartphone addiction on attention level in high school students - Şimşek, Hasan (Journal of Dependence, 2023)
Objective: Smartphones are electronic devices that have an important place in our lives today and provide many conveniences. However, it can cause many problems such as distraction and social isolation. The aim of this study is to investigate the effect of smartphone use on attention levels in high school students. Method: In the study, the smartphone addiction scale and Mesulam’s cancellation tests were applied to 100 students; 68 female, and 32 male. The obtained data were evaluated by statistical methods. Results: The average level of addiction was determined as 30.41 points. As the duration of smartphone use has increased, phone addiction has increased. Smartphone addiction was found the highest in the 90-120 mn. group (34.25±17.85) and the lowest in the 1-30 mn. group (14.50±3.53). In addition, according to the findings of attention tests, distraction occurs as smartphone use time increases, and it has been determined that this distraction is more in males than females. Conclusion: The use of smartphones may have a negative effect on the level of attention of high school students, who are the target audience of the smartphone market and are preparing for an important exam. Limiting smartphone use, especially social media, which increases smartphone addiction, can have a positive effect on the level of attention.